The Pilgrim Church: Biblical, Theological and Historical Perspectives - LI, Chun (Journal of Research for Christianity in China (JRCC), 2024)
The concept of “the Pilgrim Church” has regained prominence since the Second Vatican Council. This paper analyzes the biblical foundations, theological orientations, and historical applications of “the Pilgrim Church”. While “the Pilgrim Church” differs from other church models, its biblical basis is not sufficient to define it as a stable concept. The historical application of this idea also reveals diverse interpretative approaches, suggesting that this notion as an understanding of the church still has its limitations.